Evaluation of sustainable and healthy eating behaviors and adherence to the planetary health diet index in Turkish adults: a cross-sectional study - Macit-Çelebi, Melahat Sedanur; Bozkurt, Osman; Kocaadam-Bozkurt, Betul; Köksal, Eda (Frontiers in Nutrition, 2023)
Aim: The Planetary Health Diet Index (PHDI) is a relatively new index, and studies about its relationship with eating behaviors, nutritional status, and obesity in adults are very limited. For this reason, in this study, sustainable healthy eating behaviors of individuals and compliance of their diets with PHDI were evaluated. Methods: This cross-sectional study was conducted with 1112 adults (70.1% female, 29.9% male, mean age = 28.7 years, SE = 9.47). Study data were obtained with the face-to-face interview method via a questionnaire including socio-demographic characteristics, anthropometric measurements, the Sustainable and Healthy Eating (SHE) Behaviors Scale, and 24-hour dietary recall. PHDI was evaluated for adherence to EAT-Lancet Commission recommendations. Results: The average PHDI total score was 41.5 points. Higher SHE Behaviors Scale and PHDI scores were observed in participants with education duration above eight years (p<0.05). Those with a lower SHE Behaviors Scale and PHDI score were more likely to be obese (p<0.001). The total PHDI score was positively associated with fiber, vitamin E, potassium, and folate, and negatively associated with pyridoxine and calcium (p<0.05). The total SHE Behaviors Scale score was positively associated with carbohydrates, fiber, and potassium and negatively associated with pyridoxine and calcium (p<0.05). A one-unit increase in SHE Behaviors Scale total score resulted in 5.530 unit (95%CI: 4.652; 6.407) increase; one-unit increase in education duration (years) resulted in 0.660 unit (95%CI: 0.403; 0.918) increase in PHDI total scores. Furthermore, one-unit increase in BMI (kg/m2) resulted in -0.218 unit (95%CI: -0.424; -0.013) decrease in PHDI total scores. Conclusion: The participants' PHDI index scores were low; therefore, the adherence to the EAT-Lancet recommendation was low whichmight be associated with obesity. Clinical studies evaluating the effects of adherence to sustainable diets on adequate and balanced nutrition and health outcomes are recommended.